Relationship between movement behaviours and life satisfaction in Chinese children: A cross-lagged panel analysis - XingYi Yang; Danqing Zhang; Yang Liu (PLoS ONE, 2025)
Understanding the impacts of daily movement behaviours on the well-being of children is crucial for developing effective health promotion strategies. This study examined the relationship between movement behaviours and life satisfaction (LS) using longitudinal data from a sample of primary school students. This one-year follow-up study included 683 students (8.91 ± 1.31 years old) from Shanghai, China. Information on days of moderate- to vigorous-physical activity (MVPA), days of muscle-strengthening exercise (MSE), screen time (ST), and sleep duration was measured via a self-reported questionnaire. Cross-lagged models were used to assess the relationships between movement behaviours at baseline and LS at follow-up. Path analysis showed baseline sleep duration was a significant predictor of subsequent LS. Sex-specific models indicated baseline LS and sleep duration were predictors in males, and baseline MVPA, MSE, and sleep duration in females. Grade-specific models revealed positive relationships of baseline MSE and sleep duration with LS in Level 1 (grade 1 and 2), and baseline MVPA and MSE in Level 2 (grade 3 and 4). This study shows a complex interplay between 24-hour movement behaviours and LS among children. While baseline sleep duration emerged as a consistent predictor of LS at follow-up across the overall sample, the influence of MVPA, MSE, and ST varied by sex and grade level. These results highlight the importance of considering a range of lifestyle factors, including sleep and physical activity, in understanding and potentially enhancing life satisfaction in childhood.